Vegetation analysis of rawa singkil wildlife reserve in Rantau Gedang Village, Singkil Distric, Aceh Singkil Regency, Aceh Province. Issue 1 (February 2021) - Sugianto, S; Muslih, A M; Ar-Rasyid, U H; Anhar, A
Abstract: Rawa Singkil Wildlife Reserve plays an important role in protecting the environmental services. It contains, particularly as a protective balance of water systems and natural warehouses for carbon storage to mitigate the effects of global warming. However, the existence of Rawa Singkil Wildlife Reserve is disturbed by human activities without paying attention to the impact of natural balance. The research objective is to identify plant diversity and vegetation cover classification. This study was carried out using a rectangular path method for various stages including seedlings, saplings, poles, and trees. The results provide information on the condition of the vegetation structure and composition of various stages of tree growth. There are 25 types of vegetation found in Rawa Singkil Wildlife Reserve, which consists of three stages, namely saplings, poles, and trees. Based on the Importance Value Index analysis that Nyamplung ( Calophyllum inophyllum ) has the highest Importance Value Index, the highest Importance Value Index in the pole stage is Beras-Beras ( Syzygium zeilanicum ), and In the tree stage the highest index of importance was Ubar Susu ( Glutta renghas ) and Pucuk Merah ( Syzigium myrtifolium ).